Experiment planning at the pharmaceutical development of liposomal cytostatics - Stadnichenko, A. V.; Krasnopolsky, Yu. M.; Yarnykh, T. G. (Національний фармацевтичний університет, 2017)
At present, there is an increasing interest in developing new ways of drug delivery and targeted therapy, using nanotechnology and nanomaterials. Aim – to study the order of carrying out of pharmaceutical development of liposoms with cytostatics. Propose the scope of the experiment to optimize the planned quality indicators and technological parameters. Materials and methods. Analysis of normative documents, scientific literature and also the results of previous personal experimental studies, which became the basis for determining the methodology for the creation of liposomal drugs based on oxaliplatin and irinotecan. Lipids manufactured by Lipoid, Germany, were used to make liposomes. The lipid film was produced on a Buchi 210 rotary evaporator with a vacuum controller, at a residual pressure of 0.02 atm. For homogenization, a high pressure extrusion method was used, which was carried out on a Microfluidiser M-110P (Microfluidics, USA). Results and discussion. With the development of the pharmaceutical industry, there is a growing interest to the use of nanotechnology and nanomaterials. One of the practical implementation of nanotechnology is liposomes with cytostatics. Concentration of the active substance; pH and salt API; method of loading for API into liposomes; lipid to lipid ratio, lipids concentration; particle size and internal volume; lipid solubility in the step of lipid film preparation; stability testing of of finished products are factors that need to be studied and solved for the successful implementation of the development. Planning an experiment in the pharmaceutical development of liposomal oxaliplatin and liposomal irinotecan are complex studyes with using the principles of Quality by Design (QbD). Conclusions. The requirements of normative documentation for creating liposomal forms of medicinal products are considered. At pharmaceutical development it is necessary to use the complex approach as the majority of the put questions can not be solved separately. An experiment planning system for the pharmaceutical development of liposomal preparations of irinotecan and oxaliplatin is proposed.

На теперішній час зростає інтерес до розробки нових засобів доставки ліків і до цільової терапії при використанні нанотехнологій і наноматеріалів. Мета – вивчити порядок проведення фармацевтичної розробки ліпосомальних форм цитостатиків, запропонувати обсяг експерименту для оптимізації запланованих показників якості і технологічних параметрів. Матеріали та методи. Аналіз нормативних документів, наукової літератури, а також результатів попередніх особистих експериментальних досліджень, які стали підґрунтям для визначення методології створення ліпосомальних препаратів на основі оксаліплатину та іринотекану. Для виготовлення ліпосом використовували ліпіди виробництва Lipoid, Німеччина. Ліпідну плівку отримували на роторному випарнику Buchi 210 з вакуумним контролером при залишковому тиску 0,02 атм. Для гомогенізації використовували метод екструзії при високому тиску на установці Microfluidiser M-110P (Microfluidics, США). Результати та їх обговорення. З розвитком фармацевтичної науки зростає інтерес до використання нанотехнологій і наноматеріалів. Одним з перспективних напрямків є ліпосоми з цитостатиками. Концентрація діючої речовини, рН, метод завантаження активного компонента в ліпосоми; співвідношення компонентів і концентрація ліпідів у мембрані; розмір часток; розчинність ліпідів при виготовленні плівки; параметри гомогенізації; режим ліофілізації; стабільність після регідратації; дослідження стабільності готових лікарських форм впродовж терміну придатності – фактори, які необхідно вивчити для успішної реалізації розробки. Планування експерименту з фармацевтичної розробки ліпосомальних форм оксаліплатину та іринотекану є комплексним дослідженням з використанням принципів Quality by Design (QbD). Висновки. Розглянуті вимоги нормативної документації для створення ліпосомальних форм лікарських препаратів. У фармацевтичній розробці необхідно використовувати комплексний підхід, оскільки більшість питань неможливо вирішити окремо. Запропоновано систему планування експерименту у фармацевтичній розробці ліпосомальних препаратів іринотекану і оксаліплатину.
Планування експерименту при фармацевтичній розробці ліпосомальних препаратів цитостатиків
Keywords: irinotecan; oxaliplatin; liposomes; lipid bilayer; pharmaceutical development; chromatography; freeze drying; іринотекан; оксаліплатин; ліпосоми; бішар ліпідний; розробка фармацевтична; хроматографія; ліофілізація